2007
DOI: 10.1111/j.1365-2524.1994.tb00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Policy and practice: fundamental contradictions in the conceptualization of community care for elderly people?

Abstract: For more than two decades, community care has been proclaimed the answer to the 'social problem' of the ageing of the population. Since the publication of the Community Care Whit(. Paper (Department of Health 1989), a plethora of discussion and guidance documents have followrd. In this paper, critical examination is made of some of the assumptions that appear to underpin policy and debate about community care. It is argued that recent policy and community care reforms may be affected adversely by inherent conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Researchers have argued for some time that this amalgam of client needs and operational imperatives not only compromises the needs-led quality of the assessment but also undermines the whole assessment process by replacing the validated measures at its core with an expert option assessment based on subjectively defined notion of "need" (Caldock, 1994;Ellis, 1993;Hardy, Young, & Wistow, 1999;Richards, 2000); unsurprisingly, it has been found that this kind of approach leads to inconsistent care outcomes (Caldock, 1994;Ellis, 1993;Hardy et al, 1999;Richards, 2000). Self-or co-assessment approaches harbor the promise to address some of these issues.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Researchers have argued for some time that this amalgam of client needs and operational imperatives not only compromises the needs-led quality of the assessment but also undermines the whole assessment process by replacing the validated measures at its core with an expert option assessment based on subjectively defined notion of "need" (Caldock, 1994;Ellis, 1993;Hardy, Young, & Wistow, 1999;Richards, 2000); unsurprisingly, it has been found that this kind of approach leads to inconsistent care outcomes (Caldock, 1994;Ellis, 1993;Hardy et al, 1999;Richards, 2000). Self-or co-assessment approaches harbor the promise to address some of these issues.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Moreover, it has been argued that the very use of terms such as 'need' and 'care' places people in a dependent position, reinforcing the perception that they are problematic (Caldock 1994a). Therefore, rather than assessment starting with the hopes and aspirations of users and carers (Middleton 1994), the tendency is for it to focus on deficits and difficulties.…”
Section: Assessment: Putting Rhetoric Into Practicementioning
confidence: 99%
“…At a conceptual level, there is a lack of clarity about the definition of key concepts. At the most fundamen-tal level, there is only limited agreement on the parameters and objectives of assessment (Caldock 1993, Higgins et al 1994 with no clear understanding about what notions of 'empowerment' (Department of Health 1993) or 'needs-led' (Baldwin & Woods 1994, Caldock 1994a) actually entail. As a recent official monitoring exercise has highlighted, it is apparent that in many areas:…”
Section: Assessment: Putting Rhetoric Into Practicementioning
confidence: 99%
See 2 more Smart Citations